THE PATHOLOGICAL MANIFESTATIONS OF INTRAPLEURAL AD HESION - Alexandr Alexandrovich Vorobyev; Anton Vladimirovich Kalashnikov; Dmitry Shamilyevich Salimov (Современная наука и инновации, 2022)
The article presents the results ofthe analysis and evaluation ofthe clinical significance of intrapleural adhesion. The absence of pathological manifestations intrapleural adhesion. Formulated the concept of strengthening adhesiveness to stabilize the thorax in polytrauma.